Ambiguity in the Policy Implementation of the No-Smoking Area: Evidence from Indonesia - Abdul Muin Hafied; Husain Syam; Hamsu Abdul Gani; Haedar Akib; Rifdan Rifdan (Program Pascasarjana Universitas Negeri Makassar, 2024)
The ambiguity in the implementation of the No-Smoking Area (NOSAR) public policy is a topic of discussion among people occasionally, along with the underlying perspective of its users (smokers). This article explains the implementation of the NOSAR policy. Qualitative research methods with a phenomenological approach were used to reveal the meaning behind the facts of implementer and smoker behavior. The data collection technique is through observation at the locus where markers or writing are placed that inform about the prohibition of smoking. Apart from that, in-depth interview techniques were used with informants, both policy implementers and active smokers and passive smokers, while exploring documents regarding regulations regarding NOSAR in Bekasi City Government agencies, Indonesia. The data analysis follows an interactive model: data collection, condensation, data presentation, and verification/conclusion. The results of the research found that the implementation of the NOSAR policy in the City of Bekasi has been implemented effectively. However, there are still various obstacles found in the context of its implementation, including a lack of proportional human resources and funds for implementing regional regulations, a lack of coordination between agency leaders and employees, the implementation of trials Justice for NOSAR violators is limited to giving verbal warnings and no administrative sanctions have been given, so that violations of the rules in the NOSAR are still often found.